Factors Influencing Food Insecurity in Nepal - Regmi, Hem Raj; Rijal, Kedar; Joshi, Ganesh Raj; Sapkota, Ramesh P.; Thapa, Sridhar (Journal of Institute of Science and Technology, 2019)
Nepal has been persistently encountering food insecurity and under-nutrition. It is therefore utmost important to determine the factors responsible for influencing food insecurity in Nepal. This study examines the factors determining food insecurity in Nepal applying binary logistic models for food poverty, household with inadequate food consumption and poor dietary diversity using data from Nepal Living Standard Survey 2010/11. Food security was determined to be strongly associated with education level and age of household head, household with higher female education level, larger farm size with higher ratio of irrigated land, better access to markets, roads and cooperatives, better household assets and remittance recipient households. Food insecure is relatively more prevalent in rural areas with higher dependent on rain-fed agriculture, higher dependency ratio and larger family size. Improving both physical and economic access to foods, together with investment in education and agriculture could help to reduce food insecurity and hunger from Nepal.